2013
DOI: 10.1249/mss.0b013e318296d7b8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and Academic Performance in Finnish Children

Abstract: In this study, self-reported physical activity was directly, and screen time inversely, associated with academic achievement. Objectively measured physical activity and sedentary time were not associated with academic achievement. Objective and subjective measures may reflect different constructs and contexts of physical activity and sedentary behavior in association with academic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
117
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 28 publications
18
117
2
8
Order By: Relevance
“…However, in Finland, self-reported PA was directly associated with academic achievement; but, objectively measured PA was not associated with academic achievement (12); and among first-year university students in Switzerland, better PA did not predict better learning goal achievement; and day-to-day PA was not related to daily learning goal achievement (47). As for the second indicator of academic achievement, we observed that none of the four PA forms was significantly associated with the subjective importance of achieving good grades.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, in Finland, self-reported PA was directly associated with academic achievement; but, objectively measured PA was not associated with academic achievement (12); and among first-year university students in Switzerland, better PA did not predict better learning goal achievement; and day-to-day PA was not related to daily learning goal achievement (47). As for the second indicator of academic achievement, we observed that none of the four PA forms was significantly associated with the subjective importance of achieving good grades.…”
Section: Discussionmentioning
confidence: 82%
“…Studies in Finland (children) and elsewhere (adolescents) reported a positive association between PA and academic achievement (12,13). In contrast, in Kuwait, there was no direct association between PA and academic achievement (14); and in the UK, there was no direct association between PA and students' academic achievement whether the indicator employed was subjective (self reported) or objective (actual module grade) (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between fitness and all-cause mortality Syvaoja et al, 2013) and between physical activity and all-cause mortality (Lee and Paffenbarger, 2000;Paffenbarger et al, 1994) have been described. However, only few studies have investigated the association between different domains of physical activity and allcause as well as cause-specific mortality, and the evidence is inconsistent (Andersen et al, 2000;Arrieta and Russell, 2008;Autenrieth et al, 2011;Barengo et al, 2004;Besson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies which investigated the association between PAL and academic performance have found a positive relationship between academic performance and PAL, especially regarding vigorous activities 18,19 however, others have not found this association 20,21 . Morales et al 22 found a linear relation between self-reported daily PAL and academic performance.…”
Section: Discussionmentioning
confidence: 99%